Effect of thyroxin and cortisol on the hatching of eggs, larval morphometry and survival of Heteropneustes fossilis (Bloch) larvae - Nayak, P K; Mishra, T K; Ayyappan, S (Indian Journal of Fisheries, 2011)
Fertilized eggs of Indian catfish (Heteropneustes fossilis) were exogenously treated with L-thyroxin (T4; 0.05 mg/l), cortisol (0.5 mg/l) and cortisol + T4 (0.5 mg/l + 0.05 mg/l, respectively) by bath/immersion after three hours of fertilization up to 15 days of age to examine their effect on earlier development growth and survival of larvae. Growth and survival of larvae were significantly improved (P<0.001) in the treated groups as compared to controls. The experiments also suggest the advanced digestive function induced by T4 and cortisol treated group, which was evident for the improvements in the food utilization during the critical phases of first feeding and promoted one or more vital development processes that result in uniform growth, decreased mortality, transformation of larvae to juvenile stages resulting in better survival under compromised condition. Frequency of deformities was reduced by combined treatments of hormones. The current study suggests the interactive hormonal regulation of developmental processes, working within the context of other biological variables, improve the hardiness of small larvae. Therefore, this combined therapy is emerging as an aquaculture remedy and may have practical utility in fish hatchery practice to help better larval rearing success